An Analysis of Commissive Speech Act Used by The Shopping Hosts of MNC Shop - Widdya Syafitri (JURNAL ARBITRER, 2019)
This research focuses on the use of commissive speech act used by the shopping hosts of MNC Shop. The source of data is taken from the advertisements of household appliances, such as frying pan, rice cooker, vacuum cleaner, etc which are broadcasted in December 2018. The purposes of the research are to identify and to explain the form and the pattern as well as the function of the commissive speech acts used by the shopping hosts. This research uses qualitative approach. The data are collected by using observational method followed by recording and note-taking technique. Then, the data are analyzed by using pragmatic identity method and distributional method with deletion and permutation technique. The theory of form and pattern of the commissive speech act are based on Alwi's and Putrayasa's theory. Meanwhile the theory of its function is taken from Yule's and Ibrahim's theory. From the analysis, it is found that the commissive speech acts in the advertisement can be uttered in the form of declarative, interrogative and exclamative. The pattern can be in the form of normal sentence (subject preceding the predicate then followed by the object) or in the form of inverted sentence (the inversion of normal pattern) which the predicate preceding the subject, etc. In terms of its functions, the commissive speech acts can be used to promise, to guarantee and to convince.